Electrical and Protrusion Stimulation System for Braille Recognition Training - Jeong, Hakyeong; Hwang, Myungin; Yeom, Hojun (International Journal of Engineering and Technology, 2018)
As the number of blind people increases due to acquired factors, the necessity of a device capable of recognizing the braille quickly and accurately has been increased, and research is underway to develop a braille device for enhancing the readability of the braille. This study suggests a system to increase the recognition rate of braille by fusing visual information through tongue electrical stimulation device and Braille output device based on the protruding tactile sensation based on the method of applying electrical stimulation to the tongue. In particular, considering Korean Braille characteristics and Braille recognition error, we propose a system to increase the Braille resolution by separating the consonants into protruded Braille output devices of servo motor type and Braille output device of electrical stimulation type. Â Â